Akibat Hukum Terhadap Pengurusan Biaya Nafkah dan Pendidikan Anak Pasca Perceraian - I Putu Yoga Febrian Cahya; I Nyoman Putu Budiartha; Ni Komang Arini Styawati (Fakultas Hukum, Universitas Warmadewa, 2021)
Responsibility for parents to their children is an obligation that should be carried out by every parent. Children get all the important rights to support their growth and development and are entitled to the best possible custody of their parents. The end of the marriage between the wife and husband does not abolish all the obligations of parents to their children. The purposes of this study are to determine the responsibility of parents to children after their parents' divorce and the legal consequences for parents who do not carry out their obligations. This research uses a normative research type with a statutory approach and a conceptual approach. The technique of collecting legal materials is done by applying a literature study. Sources of legal materials in the form of primary, secondary, and tertiary legal materials which are then analyzed using the method of processing legal materials systematically and the results are presented descriptively. The results of the study indicate that the management of child support costs can be seen from the Civil Code, the 2019 Law on Marriage, Law Number 35 of 2014, Law Number 4 of 1979 concerning Welfare. The legal consequences for both parents who do not carry out their obligations can be done in 2 (two) ways, namely Application for Execution and Revocation of Custody to the Religious Court.